Reduction and coisotropic invariant tori of Hamiltonian systems with non-poisson commutative symmetries. II - Parasyuk, I. O. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
Haamiltonian systems of mechanical type are considered on a twisted cotangent stratification of a manifold admitting a smooth free torus action. In the case where these systems possess non-Poisson symmetries generated by the torus action, the Lee-Cartan reduction scheme is described and the structure of a reduced phase space and reduced Hamiltonians is clarified.